Особливості методів визначення температурних аномалій за даними ДЗЗ MODIS (TERRA) та AVHRR (NOAA). Оцінки їх якості - Вишняков, В.Ю.; Ткачук, П.А. (Екологічна безпека та природокористування, 2012)
In article the paper deals with methods for processing data of remote sensing (RS) from TERRA satellites and NOAA to determine the temperature anomalies in Ukraine. Presented by the developed algorithm analysis compliance fire temperature anomalies actual fire according to Ministry of Emergency Situations of Ukraine and shows a results.